Influence of hypoxic interval training and hyperoxic recovery on muscle activation and oxygenation in connection with double-poling exercise - Zinner, C.; Hauser, A.; Born, D.-P.; Wehrlin, J. P.; Holmberg, H. C.; Sperlich, B. (PLOS ONE, 2015)
Here, we evaluated the influence of breathing oxygen at different partial pressures during recovery from exercise on performance at sea-level and a simulated altitude of 1800 m, as reflected in activation of different upper body muscles, and oxygenation of the m. triceps brachii. Ten well-trained, male endurance athletes (25.3 +/- 4.1 yrs; 179.2 +/- 4.5 cm; 74.2 +/- 3.4 kg) performed four test trials, each involving three 3-min sessions on a double-poling ergometer with 3-min intervals of recovery. One trial was conducted entirely under normoxic (No) and another under hypoxic conditions (Ho; FiO2 = 0.165). In the third and fourth trials, the exercise was performed in normoxia and hypoxia, respectively, with hyperoxic recovery (HOX; FiO2 = 1.00) in both cases. Arterial hemoglobin saturation was higher under the two HOX conditions than without HOX (p<0.05). Integrated muscle electrical activity was not influenced by the oxygen content (best d = 0.51). Furthermore, the only difference in tissue saturation index measured via near-infrared spectroscopy observed was between the recovery periods during the NoNo and HoHOX interventions (P<0.05, d = 0.93). In the case of HoHo the athletes' P-mean declined from the first to the third interval (P < 0.05), whereas P-mean was unaltered under the HoHOX, NoHOX and NoNo conditions. We conclude that the less pronounced decline in P-mean during 3 x 3-min double-poling sprints in normoxia and hypoxia with hyperoxic recovery is not related to changes inmuscle activity or oxygenation. Moreover, we conclude that hyperoxia (FiO2 = 1.00) used in conjunction with hypoxic or normoxic work intervals may serve as an effective aid when inhaled during the subsequent recovery intervals.